Solve 2x-3/y=9 and 3x+7/y=2 by Elimination and Substitution Method

Solve: 2x-3/y=9 and 3x+7/y=2

Elimination Method

2x-$\frac{3}{y}$=9 —-(i)

3x+$\frac{7}{y}$=2—-(ii)

Multiplying Equation (i) by 7 and Equation (ii) by 3 we get,

14x – $\frac{21}{y}$ = 63 —(iii)

9x + $\frac{21}{y}$ = 6 —-(iv)

Adding Equations (iii) and (iv) we get,

14x – $\frac{21}{y}$+9x + $\frac{21}{y}$ =63+6

⇒ 23x = 69

⇒ x= $\frac{69}{23}$

⇒ x = 3

Substituting the value of x in equation (i) we get,

2(3) – $\frac{3}{y}$ = 9

⇒ 6 -$\frac{3}{y}$=9

⇒ 6-9=$\frac{3}{y}$

⇒ -3=$\frac{3}{y}$

⇒ -3y=3

⇒ y= $\frac{3}{ – 3}$

⇒ y=-1

∴ Required Solutions are x = 3 , y=-1 [Ans]

Substitution Method

2x-$\frac{3}{y}$=9 —-(i)

3x+$\frac{7}{y}$=2—-(ii)

From Equation (i) we get,

2x-$\frac{3}{y}$=9

⇒ 2x = $\frac{3}{y}$ +9

⇒ 2x=$\frac{3 + 9y}{y}$

⇒ x = $\frac{3 + 9y}{2y}$ —-(iii)

Substituting the value of x in equation (ii) we get,

3x+$\frac{7}{y}$=2

$3\left(\frac{3 + 9y}{2y}\right) + \frac{7}{y} = 2$

$\Rightarrow \frac{9 + 27y}{2y} + \frac{7}{y} = 2$

$\Rightarrow \frac{9 + 27y + 14}{2y} = 2$

$\Rightarrow 23 + 27y = 4y$

$\Rightarrow 23 = 4y – 27y$

$\Rightarrow 23 = – 23y$

$\Rightarrow y = \frac{23}{ – 23}$

$\Rightarrow y = – 1$

From equation (iii) we get,

${\mathrm{x}} = \frac{3 + 9{\mathrm{y}}}{2{\mathrm{y}}}$

$\Rightarrow {\mathrm{x}} = \frac{3 + 9( – 1)}{2( – 1)}$

$\Rightarrow {\mathrm{x}} = \frac{3 – 9}{ – 2}$

$\Rightarrow {\mathrm{x}} = \frac{ – 6}{ – 2}$

$\Rightarrow {\mathrm{x}} = 3$

∴ Required Solutions are x = 3 , y=-1 [Ans]

error: Content is protected !!